(untitled) (European Journal of Pure and Applied Mathematics, 2013)
In this paper we show that the left operator and right operator semi groups of a Î“-semigroup with unities are Morita equivalent monoids. It is also deduced that if L and R are two Morita equivalent monoids then a Î“-semigroup with unities can be constructed such that its left and right operator monoids are isomorphic to L and R respectively. This result is used to obtain some properties of monoids which remain invariant under Morita equivalence.Â